Cumulus Cells Are Potential Candidates for Cell Therapy - Mohammed, Eslam Essam; Yilmaz, Sema; Akcin, Oya Alagoz; Nalbantoglu, Barbaros; Ficicioglu, Cem; Sahin, Fikrettin; Coban, Esra Aydemir (INT INST ANTICANCER RESEARCH, 2019)
Background/Aim: Cumulus cells (CCs) originate from the membrane granulosa cells and surround oocytes during follicle maturation. CCs produce high levels of hyaluronan that targets CD44, which is a major tumorigenic marker. This study aimed to investigate whether CCs have a role in cell therapy by targeting CD44 in pancreatic cancer cells. Materials and Methods: CCs were isolated from the oocytes and incubated in a hypoxic environment. BxPC-3 pancreatic cancer cells were treated with CC conditioned media for three days. Results: Conditioned media of CC cells incubated in hypoxic conditions caused a 25% reduction in the viability of BxPC-3 cells. Expression of anti-apoptotic genes was down-regulated, while that of pro-apoptotic genes was upregulated. An increased number of BxPC-3 cells exhibited increased levels of reactive oxygen species and arrested in the synthesis (S) phase of the cell cycle. Conclusion: CCs conditioned medium induced apoptosis of pancreatic cancer cells.
Keywords: BxPC-3; granulosa cells; oocyte; pancreatic cancer; HYALURONIC-ACID; CD44; INHIBITION; MATURATION; REGULATORS; INDUCTION; OVULATION; BIOLOGY; Research & Experimental Medicine